High-resolution measurements of scattering in wheat canopies-implications for crop parameter retrieval - Morrison, Keith; Brown, Sarah C. M.; Quegan, Shaun; Bennett, John C.; Cookmartin, Geoff (IEEE, 2006)
Polarimetric X- and C-band measurements by the University of Sheffield ground-based synthetic aperture radar(GB-SAR)indoor system provide three-dimensional images of the scattering processes in wheat canopies, at resolutions of around a wavelength (3–6 cm). The scattering shows a pronounced layered structure, with strong returns from the soil and the flag leaves, and in some cases a second leaf layer. Differential attenuation at horizontal (H) and vertical (V) polarization, due to the predominantly vertical structure of the wheat stems, gives rise to marked effects. At both C and X bands, direct return from the canopy exceeds the soil return at large incidence angles for VV polarization, but is comparable to or less than the soil return in all other cases. At HV, the apparent ground return is probably due to a double-bounce mechanism, and volume scattering is never the dominant term. Direct sensing of the crop canopy is most effective at X band, VV, and large incidence angles, under which conditions the return is dominated by the flag leaf layer. Field measurements with the outdoor GB-SAR system suggest, however, that for sensitivity to biomass and reduced susceptibility to disturbances by rainfall, a two-channel C-band system operating at a medium range of incidence angles is preferred.